THE HISTORICAL DEVELOPMENT OF PANCASILA IN INDONESIAN NATIONAL LIFE - Kurnia Ali Syarif (EDUSOS: Jurnal Edukasi dan Ilmu Sosial, 2026)
Pancasila is the philosophical foundation and ideological identity of the Indonesian nation that originated from the historical, cultural, religious, and social values of Indonesian society. This study aims to analyze the historical development of Pancasila, including the values that existed before Indonesian independence, the process of its formulation and ratification as the foundation of the state, and its development from the Old Order period to the Reform era. This research employed a qualitative method using a library research approach. Data were collected through documentation studies from books, scientific journals, official documents, and other relevant academic sources discussing the history and development of Pancasila. The collected data were analyzed using descriptive qualitative analysis to provide a systematic understanding of the role and implementation of Pancasila throughout Indonesian history. The results of the study indicate that the values of Pancasila had existed long before independence through traditions such as mutual cooperation, deliberation, tolerance, and social justice within Indonesian society. The formulation of Pancasila was carried out through discussions, debates, and compromises among Indonesian national leaders before being officially established as the ideological foundation of the state. Furthermore, the implementation of Pancasila has experienced various political and social dynamics across different governmental periods. The novelty of this study lies in its comprehensive discussion of the historical development, political transformation, and contemporary challenges of Pancasila in the era of globalization and digital transformation.